2023
DOI: 10.1152/ajpheart.00552.2022
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related external factors influence pulmonary vascular angiogenesis in a sex-dependent manner

Abstract: Bronchopulmonary dysplasia (BPD) is a devastating disease with a significant sexual dimorphism where males have a disadvantage compared to their female counterparts. Although mechanisms behind this sexual dimorphism are poorly understood, sex differences in angiogenesis have been identified as one possible source of the male disadvantage in BPD. Pulmonary angiogenesis was assessed in vitro using a bead sprouting assay with pooled male or female human pulmonary microvascular endothelial cells (HPMEC, 18-19 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The creation and then subsequent refinement and remodeling of a self-assembled vascular plexus results in a highly efficient hierarchical architecture. However, all vascular networks are not the same; studies have demonstrated that microvascular networks are distinct within different tissues and vary with sex (6770). Remodeling of vascular networks is, in part, regulated by fluid flow and the local mechanical microenvironment and these factors continue to play a significant role in proper endothelial function throughout the entirety of the vessel lifespan (7173).…”
Section: Discussionmentioning
confidence: 99%
“…The creation and then subsequent refinement and remodeling of a self-assembled vascular plexus results in a highly efficient hierarchical architecture. However, all vascular networks are not the same; studies have demonstrated that microvascular networks are distinct within different tissues and vary with sex (6770). Remodeling of vascular networks is, in part, regulated by fluid flow and the local mechanical microenvironment and these factors continue to play a significant role in proper endothelial function throughout the entirety of the vessel lifespan (7173).…”
Section: Discussionmentioning
confidence: 99%
“…and naturally derived (e.g., collagen, hyaluronic acid, alginate, fibrin, etc. ), have been used for studies that mimic the ECM and can also allow for embedding stromal cells within the bulk of the hydrogel (22)(23)(24)(25); however, independent control of biophysical properties and protein or peptide identity are difficult and require more care.…”
Section: Introductionmentioning
confidence: 99%